A horizontally transferred bacterial gene aids the freezing tolerance of Antarctic bdelloid rotifers - James A. Raymond (Proceedings of the National Academy of Sciences, 2025)
Bdelloid rotifers are well known for their abilities to survive long periods of freezing as well as acquire foreign genes. Recently sequenced genomes of some bdelloid rotifers in England were found to encode several proteins similar to ice-binding proteins (IBPs) that are usually associated with freeze–thaw tolerance. Here, I describe bdelloid rotifers inhabiting an algal patch in Antarctica that have multiple homologs of these genes. Structures of the proteins predicted by AlphaFold show that they are well designed for ice-binding and a recombinant protein made for one of them showed strong ice-binding activity. The existence of multiple copies of these proteins is another characteristic of IBPs. Furthermore, multiple bdelloid rotifers in the algal patch were revived in less than an hour after storage at −25 °C for 24 y, an apparent record for laboratory-controlled studies. Several characteristics of these genes point to bacteria as their source: sequence homology, absence of introns, and a structural peculiarity so far found only in bacteria. The remarkable freezing tolerance of bdelloid rotifers can thus be at least partially attributed to horizontally acquired bacterial genes encoding IBPs.